Pertanggungjawaban Pidana Notaris Terhadap Pemalsuan Akta Autentik - Givanti, Dofana; Rasji, Rasji (Universitas Ekasakti, 2023)
The purpose of writing this article is to be able to know and analyse how the notary's liability for forgery of authentic deeds. This article uses normative research type with statutory research approach and conceptual approach, and uses descriptive qualitative data analysis with deductive thinking method. Criminal offences by notaries for the act of forgery of authentic deeds can be subject to sanctions contained in the Criminal Code with applicable provisions, in this case, namely the criminal act of forgery. Notaries who commit criminal offences must be punished, and the Criminal Code in general can be applied to the Notary in accordance with the principle of lex specialis derogate legi generali which is interpreted a contrario, namely as long as there is no regulation regarding criminal sanctions in the UUJN specifically, the provisions of general criminal sanctions (Criminal Code) will apply. Criminal responsibility carried out by the Notary, namely for the criminal act of forgery of authentic deeds, namely by going through the process in the Criminal Justice System related to the submission of allegations of forgery of authentic deeds starting from the investigation process to the trial. Falsification of an authentic deed made by a notary has implications for the authentic deed to be null and void.